Supporting Factor Analysis in Health Promotion Hospital in Muhamadiyah Hospital, Lamongan - Al-Aufa, B; Dewi Sartika, R A (KnE Social Sciences, 2018)
Implementation of health promotion hospital is deemed not quite good enough. Although, health promotion has been implemented in Lamongan Muhammadiyah Hospital, there are still problems that interfere the implementation. This study aimed to describe the factors that support the implementation of health promotion hospital in Lamongan Muhammadiyah Hospital. This research uses a qualitative method. Factors that influence an implementation of health promotion hospital developed by the Ministry of Health of Indonesia have been used as the conceptual framework. That concept says that the commitment of management, the existence of special unit and worker, HPH training, facilities and tools and fund influence an implementation of HPH. Interviewees have been selected using purposive sampling and snowball sampling method. Interviewees in this research are the Directors of hospital, Head and Members of HPH unit and patients. Sources of data are divided into two parts. The first part is the primary data that are the result of interview, document analysis, focus group discussion and observation, and the second part is the secondary data that are the documents that needed to answer the purpose of this study. All of the directors show that they have a commitment in the implementation of HPH. An HPH Team has been created. Hospital still do not have a special health promotion worker. HPH training is still rarely implemented. Hospitals have a good and enough facilities and tools for implementing health promotion. Funding of health promotion has been arranged by every department in the hospital. Keywords: supporting factors, health promotion hospital, qualitative approach